Contemporary considerations of the relationship between science and religion - Đurić, Drago; Nurkić, Petar (Sociološki pregled, 2024)
Modern debates on science and religion draw wide audiences due to the popularity of the subject. Yet, these audiences often lack in-depth knowledge about both fields, which leads them to firmly support one side, usually retaining their core beliefs even after the debate. This paper explores several possible relationships between science and religion: conflict, independence, dialogue, and integration. We challenge the view that science and religion are independent, operating on separate grounds, and assert that similar problems hold true for dialogue and integration. Beliefs formed at an early age are difficult to correct, and dialogue rarely alters deep-rooted convictions, frequently causing conflicts. The paper advocates that early education about the nature of science and religion is a key strategy in mitigating or preventing conflicts between the two.
Keywords: science and religion; conflict; independence; dialogue; integration